Iot baseada em phm aplicada a centrais condicionadoras de ar - Bezerra, Bemielison Gletson da Silva (Universidade Federal Rural do Semi-Árido, 2018)
In recent years, air conditioning has become more accessible to the population, either by improving the quality of life or reducing the inputs used in the construction of equipment. Driven by the technological advancements of individual components or manufacturing processes and energy matrices, concern with factors such as maintenance and reduction of energy consumption has become even greater. In general, the most commonly used maintenance option is the corrective (break-repair), which is the most costly aggregate, since until the complete failure of the equipment many components of the system may be damaged. Therefore, the costs are increased, the increase of the electric energy consumption during the period of malfunction of the equipment until the forced stop of the same. In this sense, the innovation and reduction of the components sensors and actuators, as well as of the communication technologies has enabled the monitoring of the working conditions and health prognoses of the most diverse equipment, being denominated of "Internet of Things", or IoT, the insertion of sensors and internet connection of any object that surrounds us In this work, IoT-based hardware and firmware were developed with the application of predictive maintenance techniques CBM (Condition-Based Maintenance) and PHM (Prognostics and system health management) for acquisition and data measurement of an air conditioning central, such as: active, reactive, apparent power consumption and power factor. The hardware contains three electronic boards (power, measurement and control) designed in CadSoft's Eagle software and manufactured in fiberglass printed circuit board. The firmware was implemented in the Integrated Development Environment (IDE) of the Arduino electronic prototyping platform, in communication with the remote server (Rasberry Pi computer) through an MQTT (MQTT communications server) broker. The system was calibrated; and subsequently the data acquisition and measurement tests were performed. The results obtained from the monitoring of variables and control of the air conditioner in the manual and automatic mode were quite satisfactory for this application, proving to be a useful tool in the management of maintenance and reduction of waste with electric energy
Keywords: IoT; PHM; CBM; Condicionador de Ar; Eficiência Energética; IoT; PHM; CBM; Air Conditioner; Energy Efficiency; ENGENHARIAS::ENGENHARIA ELETRICA